Competitiveness of Pepper Commodity as a Flagship Product to Compete In The Global Market - Juhari, Juhari; Susanto, Deki; Yani, Ahmad; Hasanuddin, Hasanuddin (Al-Makki Publisher, 2024)
Pepper is one of the spices that has an important function in the global food industry. Although Indonesia is one of the major pepper producers, it faces considerable challenges from competing countries such as Vietnam and Brazil. This study aims to evaluate the competitiveness of Indonesian pepper in the global market, identify factors that affect export performance, and provide strategic recommendations to improve Indonesia's position in the international market. This study uses a quantitative descriptive approach to evaluate the competitiveness of Indonesian pepper. Secondary data used are export statistics and global commodity market reports. The Revealed Comparative Advantage (RCA) and Export Product Dynamic (EPD) methods were used to analyze pepper export performance. The results showed that Indonesia experienced a decline in participation in the global value chain of pepper, with a decrease in exports from 29,692 tons in 2019 to 12,945 tons in 2022. Although Indonesia has an advantage in natural resources, it faces challenges from competing countries that have lower production costs and more efficient farming systems. Indonesia's pepper competitiveness is influenced by several factors such as product quality, innovation, and government policy support. Cooperation between the government and farmers is essential to improve the competitiveness of pepper in the international market. This study confirms that although Indonesia has great potential in pepper production, the existing challenges require serious attention. Improving Indonesia's pepper competitiveness requires the application of modern agricultural technology, product diversification, as well as stronger collaboration among all stakeholders.